Evaluasi Pelaksanaan Program Antenatal Care (ANC) Terpadu di Kabupaten Kerinci - Rizola, Clodeya; Firdawati, Firdawati; Aladin, Aladin; Sriyanti, Roza; Ramadani, Mery; Meinapuri, Malinda (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT The Sustainable Development Goals (SDGs) emphasize the reduction of the maternal mortality rate (MMR) to 70 per 100,000 live births by 2030. Despite various efforts, the MMR in Indonesia, including in Kerinci Regency, remains high. Integrated Antenatal Care (ANC) has become a key strategy in reducing maternal mortality. This study aims to evaluate the implementation of integrated ANC services in Kerinci Regency and to explore the influencing factors, including aspects of policy, input, process, and output. This research employed a qualitative approach. Informants included the Regent, Head of the District Health Office, and health workers from community health centers (Puskesmas) with the highest and lowest ANC coverage, those contributing to maternal mortality cases, and those with no reported cases. Data were collected through interviews, observations, and document review. The findings revealed that there is no specific policy regarding integrated ANC services. Implementation is hindered by a shortage of trained medical personnel and the absence of dedicated funding. The service delivery process does not fully adhere to established Standard Operating Procedures (SOPs) and remains largely top-down in planning, although coordination among health workers is relatively strong. While pregnant women reported high levels of satisfaction, the coverage of key ANC indicators (K1 and K5) remains suboptimal. In conclusion, the implementation of integrated ANC services in Kerinci Regency remains suboptimal due to various constraints in policy, input, process, and output components. This study highlights the need for short- to long-term interventions and provides in-depth insights into the challenges of implementing integrated ANC in resource-limited settings.  Keywords: Antenatal Care, Health Policy, Maternal Mortality, Program Evaluation  ABSTRAK Tujuan Pembangunan Berkelanjutan (SDGs) menekankan penurunan angka kematian ibu (AKI) 70/100.000 kelahiran hidup pada tahun 2030. Berbagai upaya telah dilakukan, AKI di Indonesia, termasuk di Kabupaten Kerinci, masih tinggi. Antenatal Care (ANC) terpadu menjadi salah satu strategi penting dalam penurunan AKI. Penelitian ini bertujuan untuk mengevaluasi pelaksanaan pelayanan ANC terpadu di Kabupaten Kerinci serta mengeksplorasi faktor-faktor yang memengaruhinya, termasuk kebijakan, input, proses, dan output. Penelitian ini menggunakan pendekatan kualitatif. Informan terdiri dari Bupati, Kepala Dinas Kesehatan, serta petugas dari Puskesmas dengan cakupan ANC tertinggi, terendah, penyumbang AKI, dan tanpa kasus AKI. Data dikumpulkan melalui wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa belum terdapat kebijakan khusus mengenai ANC terpadu, dan implementasi masih terkendala keterbatasan tenaga medis terlatih serta ketiadaan pendanaan khusus. Proses pelaksanaan belum sepenuhnya sesuai SOP dan masih didominasi perencanaan top-down, meskipun koordinasi antar petugas sudah berjalan cukup baik. Capaian indikator K1 dan K5 belum optimal, meskipun kepuasan ibu hamil tergolong tinggi. Kesimpulan penelitian ini bahwa pelaksanaan pelayanan ANC terpadu di Kabupaten Kerinci belum optimal dan masih menghadapi berbagai hambatan pada aspek kebijakan, input, proses, maupun output. Implikasi dari penelitian ini menunjukkan perlunya intervensi jangka pendek seperti rekrutmen, redistribusi dokter dan sosialisasi SOP, intervensi jangka menengah berupa pelatihan berjenjang dan penguatan pendanaan, serta intervensi jangka panjang melalui penguatan kebijakan daerah yang mendukung penurunan AKI Kata kunci: Antenatal Care Terpadu, Kebijakan Kesehatan, Angka Kematian Ibu, Evaluasi Program